Pengaruh Game Online Terhadap Kewajiban Shalat Fardhu - Teges Aryoseto, Genthur; Rudi Nurjaman, Asep; Rafid Miftah Fadhil, Muhammad; Thoriq Kirom (LPPAIK Universitas Muhammadiyah Bandung, 2023)
Technology and digital media have brought changes to the lifestyle of modern society, making it easier to access various types of entertainment, such as online games that are popular among children and teenagers. However, the impact of online games on the obligation to perform fardhu prayers is still unclear. A literature study was conducted by collecting and analyzing data from relevant sources to identify the influence of online games on the accuracy of fardhu prayer times. The results showed that online games can affect neglect of fardhu or five-time daily prayers, delayed prayer times, disrupted concentration during prayer, and some even neglecting prayer due to the addiction of playing online games. Therefore, online games still affect Muslims in fulfilling their obligation to perform fardhu or five-time daily prayers.